Business of Analytics : Measuring Up in a Digital World - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Welcome to the digital world, where anyone who uses the internet is probably a statistic. The digitisation of our lives has generated an unprecedented surge of data prompting companies to pay big money for information to be collected, dissected and analysed so as to best reach their customers and make a sale. Not many, however, are aware of how to fully exploit opportunities in the new data-driven economy, says Joe Nguyen, Senior Vice President for Asia Pacific at comScore, a global data and digital analytics firm.